The Effect Self Efficacy, Emotional Support, and Informational Support on Sexual Behavior Adolescents - Octamelia, Mega; Sabrin, Gusriani; Ratnanengsih, Ratnanengsih; Susanti, Susanti; Febrianti, Selvia (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Sexual behavior adolescents is a complex concept that influenced by developmental processes in terms of sexual maturity and reproduction. Around 33.3% of girls and 34.5% of boys started dating when they are 15 years old. Even adolescents have had sexual intercourse before the age of 15 years. Purpose: The purpose of this study was to analyze self efficacy, emotional support, and informational support on sexual behavior adolescents. Method: This research was used cross-sectional approach. This study amounted to 54 respondents with simple random sampling technique. The analysis bivariate was used spearman rank test and multivariate analysis used ordinal logistic regression. Result: The results of the Spearman test on self efficacy obtained p value = 0.000 <0.05, emotional support p = 0.000 <0.05, and informational support p = 0.035 > 0.05. These results show that there is a significant relationship between self efficacy and emotional support with sexual behavior. Ordinal logistic regression multivariate test obtained self efficacy p value = 0.000 with (Exp (B) (118) meant that adolescents who have high self-efficacy will have an influence on sexual behavior by 11.8 times higher. Conclusion: This study has effect of self efficacy on sexual behavior adolescents. Recommendation: Future researchers need to add other factors related to adolescent sexual behavior and expand the scope of research locations so that the causes of adolescent sexual behavior are more comprehensive